One‐Pot Synthesis of High‐Strained Metal Vinylidene and Metal Carbyne. Issue 54 (10th August 2022) - Huang, Fanping; Yan, Zhewei; Zheng, Xuejuan; Cai, Yapeng; Zhang, Hong; Xia, Haiping
Abstract: A novel one‐pot reaction producing a metal vinylidene structure in a five‐membered ring by cyclization of a multiyne has been achieved. The ring strain and the high stability of the cyclic metal vinylidene complexes have been analyzed experimentally and computationally. The metal vinylidene unit in a fused‐ring complex is unreactive to both nucleophiles and electrophiles. It reacts however at the nearby carbonyl group achieving the unprecedented conversion of metal tributing factors for the aromaticity‐driven process has been studied by DFT calculations. Abstract : A cyclic metal vinylidene with high ring‐strain was obtained via a one‐pot synthesis. The reactivity of this metal vinylidene with nucleophiles and electrophiles was investigated, resulting in unprecedented conversion of the metal vinylidene to a metal carbyne in five‐membered ring.